Septic Arthritis in adult patients at Chris Hani Baragwanath Academic Hospital: a clinical audit - Nhlapho, Lerato Ashford (My University, 2019)
As the third-largest hospital in the world, Chris Hani Baragwanath Academic Hospital treats a very large number of patients, many of whom are impoverished, and many who are infected with the Human Immuno-Deficiency Virus (HIV). As a referral centre, a significant number of these patients are afflicted with osteoarticular infection. We wanted to quantify this number and document the clinical, laboratory and microbiological profile of these patients. We retrospectively reviewed almost 200 cases of suspected osteoarticular infections over a four-year period. Seventy-six patients had confirmed bacterial septic arthritis, eleven had confirmed tuberculous arthritis, and there were two cases of fungal septic arthritis. The knee joint was the most commonly involved in all groups. The mean age of all the patients was 42 years (+/- 3years). The male to female ratio was 2:1. Staphylococcus aureus was the most common bacterial organism isolated (42%). There was a relatively high prevalence of Streptococcus pneumoniae (21%) in our series, most of whom (56%) had concurrent HIV infection. The HIV seroprevalence of the whole group was 51%, with a higher prevalence seen amongst the tuberculous and fungal arthritis groups. There was a statistically significant difference in the white cell count, erythrocyte sedimentation rate (ESR) and C-Reactive Protein (CRP) levels of the bacterial, tuberculous and negative arthrotomy groups (p = 0.01). Bacterial septic arthritis tends to have CRP levels above 100 mg/L and ESR levels between 50 mm/hour and 100 mm/hour. Tuberculous arthritis tends to have CRP levels between 50 mg/L and 100 mg/L, while the ESR tends to be higher than 100 mm/hour. Negative arthrotomies tend to have ESR levels around 50 mm/hour and CRP levels below 50 mg/L. Osteoarticular infection remains a big problem in developing countries, such as South Africa. There is a high rate of HIV co-infection. Uncontrolled diabetes mellitus is also a significant risk factor. Tuberculosis and fungal infections are important considerations in the immunocompromised patient. Laboratory diagnosis is challenging in adult patients. It appears that 5to 10-fold increases in CRP and ESR levels (above the normal reference ranges) have a higher positive predictive value for infection, as opposed to inflammatory arthropathies. Future research must incorporate prospective study designs and focus on the value of using other (more sensitive) laboratory tests to make the diagnosis of septic arthritis easier.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine, Orthopaedic Surgery, Johannesburg, 2019
Keywords: Church architecture; Religious architecture; Arthritis; Arthritis, Rheumatiod; Bone Diseases--therapy